GENETIC DIFFERENTIATION OF THE KAMPAR RIVER'S GIANT FEATHERBACK (Chitala lopis BLEEKER 1851) BASE ON MITOCHONDRIAL DNA ANALYSIS - Arif Wibowo; Ridwan Affandi; Kadarwan Soewardi; Sudarto Sudarto (Indonesian Fisheries Research Journal, 2010)
Although the giant featherback Chitala lopis is an important fish in Kampar River, the population structure has not been investigated. In this study, genetic diversity and population structure of giant featherback were examined using nucleotide sequence analysis of mitochondrial DNA control region for 54 fish collected from Kampar River.